Land and Lordship : Structures of Governance in Medieval Austria - Brunner, Otto, 1898-1982 (Book collections on Project MUSE., 1992)
Otto Brunner contends that prevailing notions of medieval social and constitutional history had been shaped by the nineteenth-century nation state and its "liberal" order. Whereas a sharp distinction between the public and the private might be appropriate to descriptions of contemporary society, such a dichotomy could not be projected back onto the Middle Ages. Focusing particularly on forms of lordship in late medieval Austria, Brunner found neither a "state" in the modern sense nor any distinction between the public and private spheres.Behind the apparent disorder of late medieval political life, however, Brunner discovered a coherent legal and constitutional order rooted in the the rights and obligations of noble lordship. In carefully reconstructing this order, Brunner's study weaves together social, legal, constitutional, and intellectual history.